Efektivitas Autogenic Training Terhadap Kecemasan Lansia: Literatur Review - Beba, Nova Natalia; Sjattar, Elly; Arafat, Rosyidah (Jurnal Keperawatan Muhammadiyah, 2020)
Purpose : Of this literature review writing is to determine the period of autogenic intervention.Â Method : Â that was used in gathering article was using several electronic databases including PubMed, Science Direct, DOAJ and Google Scholar, reference sources were taken manually, with limitations on articles published from 2009 - 2019, with relevant keywords.Results : The five articles used all fall into the Randomized Controlled Trial category. The results obtained from all articles that autogenic training can significantly reduce anxiety in the elderly where the p value <0.001.Conclusion : Autogenic training can be recommended as a non-pharmacological therapy to reduce anxiety in the elderly. In this study health workers have a very important role because they can do autogenic training but must have competence by attending training on autogenic training.